Hurry Up and Wait: Horology, Morality, and Irony in Cirilo Villaverde’s Cecilia Valdés o la Loma del Angel. - ANZZOLIN, KEVIN (Afro-Hispanic Review)
This article presents a literary criticism for "Cecilia Valdés o la Loma del Angel," by Cuban author Cirilo Villaverde. The author examines Villaverde's use of irony in the novel and comments on the significance of the themes of slavery and messages of abolitionism in the plot. The passage of time and the commentary on morality is also explored.